Pola Bimbingan Belajar Orangtua di Rumah dalam Pengenalan Lambang Bilangan AUD masa BDR - Engelbertus Nggalu Bali; Christine Andriani Manilani; Margatera P. E. Djokaho (JECED : Journal of Early Childhood Education and Development, 2022)
This study aims to describe the pattern of parental guidance at home in developing the ability to recognize number symbols in early childhood BDR. This type of research is descriptive qualitative research. The data collection technique was through interviews with 10 parents with early childhood, as well as observations made on the entire process of parental maturation during BDR. The results of the study describe the pattern of parental tutoring carried out through 3 stages, namely 1) directing and making agreements with children in the form of gifts (rewards) and giving punishment (punishment), 2) monitoring of practices related to the tutoring process carried out by parents, namely using 4 types of activities, namely activities of imitating, connecting and bolding number symbols, using number symbol posters and using videos learning YouTubeÂ  and games on smartphones, 3) correction of parents seeing obstacles/obstacles encountered during the learning process and solutions to overcome them as well as evaluating and not continuing. Parents have very diverse patterns and are very influential on the development of children's number symbols.Â